Effect of Midwife-Led Family-Accompanied Delivery Room Care on the Delivery Mode of Primiparas - Huang, Shangzhuan (Pacific International Journal, 2026)
Objective: To investigate the effect of midwife-led, family-accompanied delivery room care on delivery mode, labor duration, and pain intensity in primiparas. Methods: A total of 180 primiparas scheduled for vaginal delivery were enrolled and divided into an accompaniment group (n=86) and a routine care group (n=94) based on preference. The routine group received standard delivery care. The accompaniment group received midwife-led, one-to-one care in a dedicated, home-like delivery room with a family member present throughout labor and delivery. Delivery mode, durations of the first, second, and third stages of labor, pain intensity (assessed by Visual Analogue Scale, VAS), and adverse pregnancy outcomes were compared between the two groups. Results: The vaginal delivery rate in the accompaniment group (96.51%) was significantly higher than that in the routine group (76.60%, P<0.05). The durations of the first and second stages of labor were significantly shorter in the accompaniment group (8.28±0.75 h; 52.07±16.83 min) compared to the routine group (10.86±1.04 h; 63.73±22.96 min, both P<0.05). The VAS pain score during delivery was significantly lower in the accompaniment group (7.14±0.53) than in the routine group (8.22±0.72, P<0.05). The incidence of adverse pregnancy outcomes in the accompaniment group (5.81%) was significantly lower than that in the routine group (15.96%, P<0.05). Conclusion:For primiparas, implementing midwife-led, family-accompanied delivery room care can effectively increase the rate of vaginal delivery, shorten the duration of the first and second stages of labor, alleviate pain during delivery, and improve pregnancy outcomes.